CHANGES IN CONSUMER BEHAVIOR DURING THE COVID-19 PANDEMIC FROM THE PERSPECTIVE OF PLANNED BEHAVIOR THEORY - Anita Nisa Kambey; Selly Mumu; Toar Romario Sigar; Putra Petra Dungair; Tiffany Sayako Karamoy (LPPM Universitas Bina Bangsa, 2024)
The Covid-19 pandemic impacts various aspects of life, including changes in consumer behavior. This research aims to analyze how consumer behavior has changed during the COVID-19 pandemic from the perspective of planned behavior theory. The theory of planned behavior explains that attitudes, subjective norms, and behavioral control influence individual behavior. This research uses an observation method, which is demonstrated by recording consumer behavior patterns through content analysis of the content or message of a document obtained from several secondary data. This research shows that consumer behavior experienced changes during the COVID-19 pandemic, especially during implementation of large-scale social policies (PSBB).